Demographic, knowledge, attitudinal, and accessibility factors associated with uptake of cervical cancer screening among women in a rural district of Tanzania: Three public policy implications - Lyimo Frida S; Beran Tanya N (BMC, 2012)
Abstract Background Cervical cancer is an important public health problem worldwide, which comprises approximately 12% of all cancers in women. In Tanzania, the estimated incidence rate is 30 to 40 per 100,000 women, indicating a high disease burden. Cervical cancer screening is acknowledged as currently the most effective approach for cervical cancer control, and it is associated with reduced incidence and mortality from the disease. The aim of the study was to identify the most important factors related to the uptake of cervical cancer screening among women in a rural district of Tanzania. Methods A cross sectional study was conducted with a sample of 354 women aged 18 to 69 years residing in Moshi Rural District. A multistage sampling technique was used to randomly select eligible women. A one-hour interview was conducted with each woman in her home. The 17 questions were modified from similar questions used in previous research. Results Less than one quarter (22.6%) of the participants had obtained cervical cancer screening. The following characteristics, when examined separately in relation to the uptake of cervical cancer screening service, were significant: husband approval of cervical cancer screening, women's level of education, women's knowledge of cervical cancer and its prevention, women's concerns about embarrassment and pain of screening, women's preference for the sex of health provider, and women's awareness of and distance to cervical cancer screening services. When examined simultaneously in a logistic regression, we found that only knowledge of cervical cancer and its prevention (OR = 8.90, 95%CI = 2.14-16.03) and distance to the facility which provides cervical cancer screening (OR = 3.98, 95%CI = 0.18-5.10) were significantly associated with screening uptake. Conclusions Based on the study findings, three recommendations are made. First, information about cervical cancer must be presented to women. Second, public education of the disease must include specific information on how to prevent it as well as screening services available. Third, it is important to provide cervical cancer screening services within 5 km of where women reside.